Perceived Barriers Hindering the Jordanian SMEs Operating in the Food and Beverage Industry from Engaging in E-commerce: An Empirical Study - Al-Dmour, Rand; Al-Zubai, Gaith; Abuhashesh, Mohammd; Ahmad Amin, Eatedal (Jordan Journal of Business Administration, 2020)
The present study aimed to identify the barriers hindering the Jordanian SMEs operating in the food and beverage industry from engaging in e-commerce. It also aimed to identify the percentage of engagement in e-commerce among the SMEs operating in the food and beverage industry. A self-administrated questionnaire was developed to collect the required data during the year 2017. Questionnaire forms were sent via e-mail to 224 individuals (i.e., 224 SMEs). The sample consists of owners of Jordanian SMEs operating in the food and beverage industry and managers working at such SMEs. However, 139 questionnaire forms were retrieved and considered valid for statistical analysis. Thus, the response rate is 62 %. It was found that the percentage of engagement in e-commerce among the Jordanian SMEs operating in the food and beverage industry is still relatively low. It was also found that the examined barriers can significantly hinder the Jordanian SMEs operating in the food and beverage industry from engaging in e-commerce. In addition, it was found that organizational and technical barriers are the most influential barriers.